Self-efficacy as mediator of social support effects on student engagement: a PLS-SEM analysis - Dea Febrianty; Suryani Hardjo; Amanah Surbakti (Indonesian Institute for Counseling, Education and Theraphy, 2026)
The study examined the effect of social support on student engagement with self-efficacy as a mediating variable among high school students. Student engagement plays an important role in supporting academic achievement and active participation in the learning process. Social support received from family, teachers, and peers was assumed to enhance students’ confidence in their abilities, which in turn could increase their engagement in learning activities. This study employed a quantitative approach with a correlational design. Data were collected from high school students using social support, self-efficacy, and student engagement scales. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicated that social support positively affected self-efficacy and student engagement. Self-efficacy also positively affected student engagement and mediated the relationship between social support and student engagement. These results suggested that enhancing social support may strengthen students’ self-efficacy and ultimately improve their engagement in learning. Therefore, schools, teachers, and parents should provide adequate support to foster students’ active involvement in academic activities.